[Cal Poly Orchestra] (1919)
Cal Poly Orchestra, 1919-1920 school year, sitting on the steps of the Administration building. Seated on the right of the standing man is Helen Louis, pianist. This photo was published in the 1920 Polytechnic Journal. The bass drum is dated 1903 and 1916. 1903 was the first year of classes at Cal Poly, and the Cal Poly band was established in 1916. The standing man may be instructor H.N. Whitlock.